2022
DOI: 10.1371/journal.pgen.1010195
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of host and symbiont contributions to peptidoglycan metabolism based on comparative genomics of eight aphid subfamilies and their Buchnera

Abstract: Pea aphids (Acyrthosiphon pisum) are insects containing genes of bacterial origin with putative functions in peptidoglycan (PGN) metabolism. Of these, rlpA1-5, amiD, and ldcA are highly expressed in bacteriocytes, specialized aphid cells that harbor the obligate bacterial symbiont Buchnera aphidicola, required for amino acid supplementation of the host’s nutrient-poor diet. Despite genome reduction associated with endosymbiosis, pea aphid Buchnera retains genes for the synthesis of PGN while Buchnera of many o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 105 publications
0
21
0
Order By: Relevance
“…Nakabachi et al 37 demonstrated that RplA is synthesized as a protein in the maternal bacteriocyte and is transported into Buchnera cells. This horizontally transmitted gene is hypothesized to produce lytic translgycosylase for Buchnera cell wall remodeling and is largely omnipresent in Aphidoidea unlike other horizontally transferred genes that were lost in certain aphid lineages 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Nakabachi et al 37 demonstrated that RplA is synthesized as a protein in the maternal bacteriocyte and is transported into Buchnera cells. This horizontally transmitted gene is hypothesized to produce lytic translgycosylase for Buchnera cell wall remodeling and is largely omnipresent in Aphidoidea unlike other horizontally transferred genes that were lost in certain aphid lineages 38 .…”
Section: Discussionmentioning
confidence: 99%
“…D-amino acids are used to synthesize peptidoglycan and build the cell wall. Buchnera from the aphid tribe Macrosiphini (which includes M. persicae) contribute to building their own cell wall (Smith et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…S4). Especially the pathways for synthesis of the cell envelopes are intriguing, as cell wall synthesis has been demonstrated to be complemented and controlled by host encoded genes and inter-symbiont exchange of metabolites in hemipteran symbionts (Bublitz et al, 2019; Smith et al, 2021, 2022).…”
Section: Discussionmentioning
confidence: 99%